data security Enhancement of Private Message Security Using Classic Cryptography Based on Cipher Substitution Algorithms: Peningkatan Pengamanan Pesan Pribadi Menggunakan Kriptografi Klasik Berbasis Algoritma Subtitusi Chiper - Hildayanti Idrus (Sakura Publisher, 2023)
In this growing digital age, message or information security is important because more and more information or messages are vulnerable to being accessed or read by unauthorized persons. To protect the privacy and confidentiality of personal information, an effective and reliable message security system is needed. One effective way is to use cryptographic algorithms such as the cipher substitution algorithm that has been used to secure data. Implementation of a message or information security system using a cipher substitution algorithm can be an effective and reliable solution for securing private messages from attacks and unauthorized access and maintaining the privacy and confidentiality of personal information. This study uses the method of Literature Study, System Analysis, Implementation, and Testing to analyze and implement a visual basic based cipher substitution algorithm. The result of this research is an application based on Microsoft Visual Basic that can encrypt and decrypt messages/texts. The cipher substitution algorithm shows that the encryption and decryption process can maintain the security of the message that has been tested so that message security is guaranteed and confidentiality is maintained.